Morphinan derivatives with an oxabicyclo[3.2.1]octane structure as dual agonists toward δ and κ opioid receptors. (1st January 2022) - Uenohara, Yuka; Tsumura, Saori; Hirayama, Shigeto; Higashi, Eika; Watanabe, Yurie; Gouda, Hiroaki; Nagase, Hiroshi; Fujii, Hideaki
Graphical abstract: Highlights: Morphinan derivatives with an oxabicyclo[3.2.1]octane structure were designed based on a proposed active conformation of a selective KOR agonist nalfurafine. 6 R -Benzamide 7a was the most potent dual DOR/KOR agonist. 6S-Phenylacetamide 8b was potent full DOR agonist. 6-Amide morphinan derivatives with an oxabicyclo[3.2.1]octane structure would be a promising fundamental skeleton for the dual DOR/KOR agonists and/or selective DOR agonists. Abstract: The κ opioid receptor (KOR) is one of the promising targets to develop analgesics lacking morphine like side effects. To seek a novel KOR agonist we designed 6-amide derivatives with an oxabicyclo[3.2.1]octane structure based on a proposed active conformation of a selective KOR agonist nalfurafine. All the synthesized compounds strongly bound to the KOR and some compound showed KOR selectivities. 6 R -Amides were more potent and efficacious KOR agonists than the corresponding 6 S -isomers. However, most 6-amide derivatives were partial KOR agonist. Conformational analyses of 6 R - and 6 S -amide derivatives and nalfurafine well accounted for the difference of KOR agonistic activities between two diastereomers. Surprisingly, the tested N –H amides were full δ opioid receptor (DOR) agonists. Among the tested compounds 7a with benzamide moiety was the most potent dual DOR/KOR agonist. On the other hand, 6 S -phenylacetamide 8b was potent full DOR agonist with less efficacious agonist activity for the μ receptor and KOR. 6-Amide derivatives with an oxabicyclo[3.2.1]octane structure were expected to be a promising fundamental skeleton for the dual DOR/KOR agonists and/or selective DOR agonists.